The Relation Between Leadership and Expected Results from the Educational Process Within School Culture - Eger, Ludvík; Egerová, Dana (Revija za elementarno izobraževanje, 2023)
School culture is a multifaceted concept, comprising multiple dimensions. The present research explored relations between selected dimensions: between the dimension focused on shared objectives, trust in school leadership, and on a managerial approach, and the important dimension focused on the innovation process and the results expected from the education process. School leaders using the School Culture Inventory evaluated current and desired school culture in their primary schools to identify culture gaps. The research findings should help school leaders in planning to shape the culture and innovate the strategy of the schools they manage.